TULANG YANG DIHIDUPKAN DAN TULANG YANG DIKENANG: STUDI KOMPARATIF YEHEZKIEL 37:1–14 DAN TRADISI MA’NENE DI TORAJA - Ingrid Yuwiesia Allo Linggi; Revalina; Selvianti Arruan Lipu (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
This study aims to analyze the symbolic meaning of bones in Ezekiel 37:1–14 and the Ma'nene tradition in Toraja through a comparative approach within a contextual theology framework. The background of this study is based on the differences and possible meeting points between theological understandings in the biblical text and local cultural practices related to death and life. The method used is a qualitative literature study, where data is obtained from the biblical text and relevant scientific literature on Torajan culture and biblical theology. The results of the study show that in Ezekiel 37:1–14, dry bones symbolize the state of destruction and loss of hope of the Israelites who are restored through the power of God, thus presenting the theological meaning of new life and divine restoration. Meanwhile, in the Ma'nene tradition, the bones or remains of ancestors are interpreted as symbols of memory, respect, and the continuity of relations between the living and the deceased generations. Although both have fundamental differences in the source of meaning, namely between divine intervention and cultural construction, both show that bones have a symbolic dimension that goes beyond death. Therefore, through a contextual theological approach, dialogue between biblical texts and local culture can produce an understanding of faith that is more relevant, contextual, and respects local cultural wisdom without ignoring fundamental theological principles.